Analysis of lower urinary tract disease of dogs - Claudia Iveth Mendóza-López; Javier Del-Angel-Caraza; Israel Alejandro Quijano-Hernández; Marco Antonio Barbosa-Mireles (Pesquisa Veterinária Brasileira)
ABSTRACT: Lower urinary tract diseases (LUTD) include different conditions that affect the urinary bladder, urethra and prostate. The objective of this study was to determine the frequency of different related diseases, to characterize the population affected, and to determine risk factors in dogs. The clinical cases were diagnosed with LUTD through physical examination, and clinical laboratory and imaging studies. Male dogs had a greater predisposition to present a LUTD. Dogs from 3 months to 18 years with a median of 8 years were affected, and the most affected breeds were Poodle, Labrador, German shepherd, Schnauzer, Cocker Spaniel and Chihuahua. The LUTD presented with the following frequencies: bacterial urinary tract infection 34.02%; micturition disorders 22.68%; urolithiasis 20.61%; prostatic disease 14.43%; traumatic problems 8.24%. Sixty-seven per cent of the cases were specific diseases, such as uncomplicated and complicated bacterial urinary tract infections, urinary retention of neurologic origin and silica urolithiasis.